Well versed. (August 2021) - Bevan, John
Abstract : In response to articles in the June issue by Anna Starkey (pp34–38), Philip Ball (pp48–49) and Joanne O'Meara (p56), in which they discuss the power of art to visualize physics, the reformulation of physics as laws about what is and is not possible, and the value of humour in teaching.